Comment on analysis of 2222 colorectal polyps in 896 patients: A tertiary referral hospital study - Tarık Akar; Gökhan Dindar; Mustafa Şit; İlyas Tenlik; Emin Altıparmak (Turkish Journal of Gastroenterology, 2019)
-